The Florentine villa : architecture, history, society - Gobbi Sica, Grazia, 1942-; Creigh, Ursula; ebrary, Inc. (Abingdon : Routledge, 2007)
Scholarly and innovative with visually stunning line drawings and photographs, this volume provides readers with a compelling record of the unbroken pattern of reciprocal use and exchange between the countryside and the walled city of Florence, from the thirteenth century up to the present day. Defying the traditional and idealized interpretation of the Florentine Villa, the author: analyzes the economic factors that powered the investment in and building of country houses and estates from the early Renaissance times onwards, as well as the ideology and the architectural and literary models that promoted the Florentine villa explores the area between Florence and Sesto in its history, morphology and representation looks at the villas existing in the area. A contribution to the protection of the important cultural heritage of the landscape in the Florentine area and of its historic buildings, villas and gardens, this study makes engaging reading, not only for scholars and students in architecture, landscape design and social history, but also for the well informed reader interested in art, architecture and gardens.
Part One -- 1 Origins and development of the Villa -- 2 The Ideology of villa life in Florentine culture and society -- 3 Typological research and Renaissance treatises -- 4 The Garden: origin and development -- 5 Villas in the Nineteenth Century -- Part Two -- 6 The Shape of the Landscape -- 7 The History of the Area -- 8 Mapping the Area -- Part Three -- Villas in the Castello: Sesto Fiorentino area Appendix -- Six villas to visit Bibliography
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 13.-20. století; italská architektura -- 13.-20. století; vily -- Itálie -- 13.-20. století; venkovské obytné domy -- Itálie -- 13.-20. století; architektura a společnost -- Itálie -- 13.-20. století; Italian architecture -- 13th-20th centuries; villas -- Italy -- 13th-20th centuries; cottages -- 13th-20th centuries; architecture and society -- Italy -- 13th-20th centuries; Florencie (Itálie : oblast); Florence Region (Italy); monografie; e-knihy online; monographs; e-books online